Rapulsa Board as Interactive Math Learning Media in Elementary School - Nur Kholifah, Umi; Leviana Sari, Hesti; Darwati, Darwati; Kurniawan, Gilang (International Journal of Elementary School, 2025)
Learning mathematics in elementary schools often faces challenges from students, such as students' perceptions that math is a difficult and scary subject, resulting in low learning outcomes. This also occurs in grade III elementary school students where student scores in learning math are still low. This study aims to improve the learning outcomes of third grade elementary school students on the material “Rapulsa Board” (Hundreds, Tens, and Units) by utilizing the learning media of the printed board. The method used is a classroom action research approach consisting of planning, implementation, observation and reflection. The research subjects were 30 grade III elementary school students. Data were collected through observation, learning outcome tests, and documentation, then analyzed descriptively. The results showed that the application of the map board media was able to improve student learning outcomes from cycle 1 which was originally only 9 people who were complete increased to 30 people in cycle 2. The average score of students who were initially only 60 in cycle 1 increased to 84.5 in cycle 2. The application of Rapulsa boards is also proven to increase student understanding and student involvement in learning. The conclusion of this study is that the mapboard media can be an effective and interesting alternative for learning Mathematics in elementary schools.